Stimulasi Tumbuh Kembang Dan Edukasi Orang Tua Pada Balita Dengan Gizi Buruk - Lilik Sigit Wibisono; Fitratun Najizah; Ni Kadek Krisna Dwi Patrisia; Lulu'ah Feby Purwanti; Eriga Yessyra Syafitri; Dana Faricha; Panji Satria Wiguna (BADAN PENERBIT STIEPARI PRESS, 2022)
Physiotherapy is a profession that provides a form of health services for both individuals and groups in order to develop, maintain, and restore body movements and functions. Every individual has the right to get health services, one of which is physiotherapy, but the lack of public knowledge, and economic problems make people reluctant or even impossible to get these services. Nutritional status is one of the factors that can affect child development. The program to treat malnourished children is periodically conducted in January-March every year. The Semarang City Health Office collaborates with IFI Semarang City and STIKES KESDAM IV Diponegoro Department of Physiotherapy as well as from various other medical team collaborations to provide services to these toddlers. Malnourished toddlers from the Community Health Center (Puskesmas) of Semarang City were gathered at Rumah Pelangi Nusantara to receive services consisting of: Weight and TB examination, doctor's examination, psychologist, nutritionist consultation, social worker and physiotherapy. Physiotherapy itself plays a role in the detection and stimulation of the growth and development of children under five with malnutrition. IFI Semarang city is scheduled every Tuesday and Thursday to give assignments alternately to representatives of physiotherapists in each agency both from hospitals, Clinic and Homecare to come to Rumah Pelangi Nusantara to provide early detection treatment for malnourished toddlers who experience growth delays, by providing examinations, interventions in the form of exercise therapy and education to parents of toddlers. It is hoped that this activity can help in optimizing the stimulation of toddler growth and development along with increasing age and improving nutrition and weight gain.